Fimasartan-induced liver injury in a patient with no adverse reactions on other types of angiotensin II receptor blockers: A case report. Issue 47 (November 2017) - Park, Dae Hwa; Yun, Gee Young; Eun, Hyuk Soo; Joo, Jong Seok; Kim, Ju Seok; Kang, Sun Hyung; Moon, Hee Seok; Lee, Eaum Seok; Lee, Byung Seok; Kim, Kyung Hee; Kim, Seok Hyun
Abstract: Rationale: Angiotensin II receptor blockers (ARBs) are widely used for patients with hypertension, and fimasartan is a recently approved ARBs. Fimasartan can cause headache, dizziness, itching, and coughing. There have been several reports of hepatotoxicity in ARBs. However, there have not yet been published reports of the hepatotoxicity of fimasartan. Patient concerns: A 73-year-old man with hypertension experienced liver injury after fimasartan administration. He had a previous history of taking 3 types of ARBs each for more than 2 years before taking fimasartan, and there were no side effects on ARBs except for fimasartan. Diagnoses: Other factors that could cause liver injury were excluded in diagnostic tests, and fimasartan was suspected to be the causative agent. Intervention: Fimasartan was immediately discontinued and the patient was managed with supportive care via hepatotonics. Diagnoses: Other factors that could cause liver injury were excluded in diagnostic tests, and fimasartan was suspected to be the causative agent. Outcome: The liver injury due to fimasartan was confirmed by histology and accidental redosing. Lessons: We emphasize that liver function should be monitored during fimasartan administration because fimasartan may cause hepatotoxicity in patients who have no side effects with other types of ARBs. And fimasartan-induced liver injury may appear later than other ARBs.